PHYLLODES TUMOR: REPORT AND CASE STUDY AND LITERATURE REVIEW - Fernández, Víctor (2015)
The cystosarcoma phyllodes is a rare variant of breast cancer, which is formed from the stroma (connective tissue) of the breast, in contrast to carcinomas, which develop in the ducts or lobules. Phyllodes tumors are usually benign but on rare occasions may be malignant (possibility of spread). We report on a patient with this condition, which was referred to our center for tumor and pain in the right breast, 15 years of evolution, whose diagnosis was suspected by findings of ultrasound and mammography, was found in the operating room a mass of 20 cm in diameter, which was confirmed by pathology.